Daytime and Nighttime Sleep Characteristics and Pain Among Adults with Stable Heart Failure - Conley, Samantha (J Cardiovasc Nurs, 2019)
BACKGROUND: Pain and sleep disturbance are common among patients with heart failure (HF) and are associated with symptom burden, disability, and poor quality of life. Little is known about the associations between specific sleep characteristics and pain in people with HF. OBJECTIVE: Describe the relationships between nocturnal sleep characteristics, use of sleep medication, and daytime sleep characteristics and pain among people with HF. METHODS: We conducted a cross-sectional study of stable HF participants. We administered the SF36 Bodily Pain Scale, Pittsburgh Sleep Quality Index, and Sleep Habits Questionnaire, and obtained 3 days of wrist actigraphy and one night of home unattended polysomnography. We conducted bivariate analyses and generalized linear models. RESULTS: The sample included 173 participants [mean age= 60 years (SD 16.1), 65.3% (n= 113) male). Insomnia symptoms (p= .0010), sleep duration (p= .0010), poor sleep quality (p= .0153), use of sleep medications (p= .0170) and napping (p=.0029), and daytime sleepiness (p= .0094) were associated with increased pain. Patients with the longest sleep duration, who also had insomnia, had more pain (p= .0004), fatigue (p= .0028), daytime sleepiness (p= .0136), poorer sleep quality, (p< .0001) and took more sleep medications (p= .0029) than those without insomnia. CONCLUSIONS: Pain is associated with self-reported poor sleep quality, napping, daytime sleepiness, and use of sleep medication. The relationship between pain and sleep characteristics differs based on the presence of insomnia and sleep duration. Studies are needed to evaluate the causal relationships between sleep and pain and test interventions for these co-occurring symptoms.